Respuesta :

[tex]\\ \rm\rightarrowtail x^2-3x-10=0[/tex]

[tex]\\ \rm\rightarrowtail x^2-5x+2x-10=0[/tex]

[tex]\\ \rm\rightarrowtail x(x-5)+2(x-5)=0[/tex]

[tex]\\ \rm\rightarrowtail (x+2)(x-5)=0[/tex]

[tex]\\ \rm\rightarrowtail x=-2\;or\:5[/tex]

Given,

[tex]\small\bold{x² – 3x – 10 =0}[/tex]

Taking LHS,

[tex]\small\bold\red{ → }\small\bold{x^2 – 5x + 2x – 10}[/tex]

[tex]\small\bold\red{ → }\small\bold{ x(x – 5) + 2(x – 5)}[/tex]

[tex]\small\bold\red{ → }\small\bold{ (x – 5)(x + 2)}[/tex]

The roots of this equation, x² – 3x – 10 = 0 are the values of x for which (x – 5)(x + 2) = 0

Therefore,[tex] \small\bold{x – 5 = 0 \: or \: x + 2 = 0}[/tex]

[tex]\small\bold\red{ → }\small\bold{x = 5 \: or \: x = -2 }[/tex]

ACCESS MORE